2008
DOI: 10.1097/jgp.0b013e3181557b69
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping Well, Aging Well: A Descriptive and Cross-Sectional Study of Sleep in “Successful Agers” 75 and Older

Abstract: Objectives-To examine diary-based, laboratory-based, and actigraphic measures of sleep in a group of healthy older women and men (≥75 years of age) without sleep/wake complaints and to describe sleep characteristics which may be correlates of health-related quality of life in old age.Design-Cross-sectional, descriptive study. Setting-University-based sleep and chronobiology program. Intervention-None.Participants-Sixty-four older adults (30 women, 34 men; mean age 79) Measurements-We used diary-, actigraphic-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 26 publications
5
66
2
2
Order By: Relevance
“…Furthermore, contrary to much of the previous literature (for example, see 2) we found no sex differences in sleep quality. Whilst this finding was unexpected, this result conforms with other reports which have not found evidence for statistically significant sex differences in global sleep quality score measured by the PSQI (59)(60)(61)(62). An additional limitation regards our use of twins in the present study.…”
Section: Limitationscontrasting
confidence: 55%
“…Furthermore, contrary to much of the previous literature (for example, see 2) we found no sex differences in sleep quality. Whilst this finding was unexpected, this result conforms with other reports which have not found evidence for statistically significant sex differences in global sleep quality score measured by the PSQI (59)(60)(61)(62). An additional limitation regards our use of twins in the present study.…”
Section: Limitationscontrasting
confidence: 55%
“…34 The contrasting finding has been reported by the HK study, which found a prevalence of only 22% good sleep quality. This was partially due to the oversampling of women who appear more likely to report experiences of sleep disturbances compared to men.…”
Section: Discussioncontrasting
confidence: 37%
“…These percentages appear high but are also an argument underlining the idea that sleep quality is a decisive factor for successful aging. Other studies show similar results: Driscoll et al in a population of 64 persons, aged 75 and over, highlighted a significant association between a better perceived physical state of health evaluated by the SF-36 questionnaire and better sleep quality assessed by the PSQI [17]. There was also no relationship between objective sleep parameters and quality of life.…”
Section: Discussionsupporting
confidence: 61%